Времена года: стихи, рассказы, сказки / художник П. Иващенко - Иващенко П. (Читаем сами, 1990)
1-2кл Экземпляры: ф.3 (20160120) / Инвентарный номер: 035408 / Цена: 0.15 / Авт.знак: В 81 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1